Création à Lyon des deux premières écoles françaises de blessés militaires en décembre 1914 : le cas de la maison forte de la Buire - Catherine Guillot (In Situ)
In 2013, during the preparation of a heritage inventory file on a former fortified house known as the Buire castle, located in the third arrondissement of Lyon, the story came to light of the first two schools specially created in France for the war wounded. With the support of his municipal council, the mayor of Lyon, Edouard Herriot (1872-1957), decided in December 1914 to create two special professional schools for mutilated soldiers. One of these schools (Joffre) was set up in this former fortified house, whilst the other (Foch) was set up in an auxiliary hospital, which has since disappeared. The article looks in particular detail at the Joffre school, where some of the buildings are still in existence.